Clonal Fidelity of Micro-propagated Phalaenopsis Plantlets Based on Assessment Using Eighteen Ph-Pto SNAP Marker Loci - Raynalta, Erick; Elina, Juanita; Sudarsono, Sudarsono; Sukma, Dewi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Phalaenopsis amabilis is an Indonesia native orchid species having large, white flowers with yellow labellum coloration. This studies aimed to develop Phal. amabilis micropropagation methods and evaluate the regenerated plantlet fidelity. Media supplemented with Thidiazuron (TDZ) and Polyvinylpyrrolidone (PVP) and medium pH adjustment effects to induce protocorm-like bodies (PLBs) from leaf explants and proliferate secondary PLBs were investigated. Clonal fidelity among regenerated plantlets was evaluated using eighteen SNAP marker loci. The results showed that the Â½ MS medium supplemented with 3 mg L-1 TDZ and 0.5 g L-1 PVP was the best for PLB induction while the Â½ MS medium supplemented with 0.5 mg L-1 TDZ was the best for PLB proliferation. For PLB induction, the media pH was adjusted into pH=7 for efficient PLB regeneration. Based on the assessment using 18 SNAP marker loci, four variant alleles in three loci (11.8%) out of a total 34 plantlets were detected. The mutation frequency at the evaluated SNAP marker loci was 2.5 x 103 (0.25%). Changes in SNP alleles may not always result in phenotype changes and allele variant occurrences may not affect phenotype fidelity of micro-propagated Phal. amabilis plantlets. Therefore, further studies about the phenotype fidelity among plantlets are necessary.